Prophetic guidance on marketing - Musa, Muhammad Adli (AHAS KIRKHS Entrepreneurship Committee (KENT), 2022)
Marketing is basically a process to attract the interest of consumers in the products and services provided. It initially involves making the products and services noticeable and ultimately convincing potential customers of the value proposition underlying them. In doing so, many processes take place, from determining what consumers want or creating such wants by promoting the ‘need’ for an item or service. In doing so, there are many ethical considerations that must be taken into account. Being himself a person who was heavily involved in business, the Prophet صلى الله عليه وسلم was aware of the potential ethical pitfalls in the marketing of products and services. It is then not surprising that we find many Prophetic traditions that can serve as guidance in the marketing process. As we will see, over inflating the value proposition of products and services, which is quite common to attract potential customers, may be effective in increasing sales but is ethically questionable.